Sex Differences in Behavioral Sensitivities After Traumatic Brain Injury - Hoffman, Ann N.; Watson, Sonya L.; Makridis, Anna S.; Patel, Anisha Y.; Gonzalez, Sarah T.; Ferguson, Lindsay; Giza, Christopher C.; Fanselow, Michael S. (Frontiers in Neurology, 2020)
Traumatic brain injury (TBI) is associated with high rates of post-injury psychiatric and neurological comorbidities. TBI is more common in males than females despite females reporting more symptoms and longer recovery following TBI and concussion. Both pain and mental health conditions like anxiety and post-traumatic stress disorder (PTSD) are more common in women in the general population, however the dimorphic comorbidity in the TBI population is not well-understood. TBI may predispose the development of maladaptive anxiety or PTSD following a traumatic stressor, and the impact of sex on this interaction has not been investigated. We have shown that white noise is noxious to male rats following fluid percussion injury (FPI) and increases fear learning when used in auditory fear conditioning, but it is unclear whether females exhibit a similar phenotype. Adult female and male rats received either lateral FPI or sham surgery and 48 h later received behavioral training. We first investigated sex differences in response to 75 dB white noise followed by white noise-signaled fear conditioning. FPI groups exhibited defensive behavior to the white noise, which was significantly more robust in females, suggesting FPI increased auditory sensitivity. In another experiment, we asked how FPI affects contextual fear learning in females and males following unsignaled footshocks of either strong (0.9 mA) or weaker (0.5 mA) intensity. We saw that FPI led to rapid acquisition of contextual fear compared to sham. A consistent pattern of increased contextual fear after TBI was apparent in both sexes across experiments under differing conditioning protocols. Using a light gradient open field task we found that FPI females showed a defensive photophobia response to light, a novel finding supporting TBI enhanced sensory sensitivity across modalities in females. General behavioral differences among our measures were observed between sexes and discussed with respect to interpretations of TBI effects for each sex. Together our data support enhanced fear following a traumatic stressor after TBI in both sexes, where females show greater sensitivity to sensory stimuli across multiple modalities. These data demonstrate sex differences in emergent defensive phenotypes following TBI that may contribute to comorbid PTSD, anxiety, and other neurological comorbidities.